Health Education Using MAGIS Booklet to Increasing Menstrual Hygiene Perception of Teenage Girls - Innez Karunia Mustikarani; Yunita Wulandari; Anggi Widiaswati (Poltekkes Kemenkes Surakarta, 2021)
Menstrual hygiene is a component of individual hygiene in the form of maintaining health and hygiene of reproductive organs during menstruation. The perception that often arises in the community regarding menstrual hygiene is that the delivery of reproductive health information is inaccurate or incomplete, one of which is about the problem of menstrual hygiene. Booklet media is a method that challenges adolescents to learn because the messages are written using short, simple, concise sentences and packaged attractively. This research aims to determine the effect of health education with booklet to the menstrual hygiene perception of teenage girls. This research was quantitative with pre experimental design by using one-group pre-posttest design. The sampling technique used purposive sampling. The sample was 43 female students at SMP Muhammadiyah 1 Surakarta. The data collected with menstrual hygiene perception questionnaire and booklet “MAGIS (Menstrual Hygiene Sehat)”. The data analysis used Wilcoxon signed ranked test. The average age of respondents is 12.67 years old, meanwhile, the average of menarche age is 11.60 years old. The average perception before being given menstrual hygiene health education was 21 respondents (48,8%). Perception after being given menstrual hygiene health education in good category was as many as 42 respondents (97,6%). The result of data analysis showed z-5,696 and p = 0.000. The conclusion of this research shows that there is an effect of health education with the